Implantação de um sistema de aproveitamento de águas pluviais em uma indústria gráfica no município de Pato Branco - PR - Bortolozo, Andressa Sartor (2022)
Water is essential for life and its demand has been growing due to population growth and industrial and agricultural development. Brazil, despite having a large amount of fresh water, still needs to improve its distribution and conscious use. The rainwater harvesting appears as a good alternative for supplying the water demand and discharging urban drainage. The objective of this work is to elaborate the project of a rainwater harvesting system for nonpotable purposes in a printing industry in the county of Pato Branco-PR. For that, initially a bibliographic study was carried out. After that, rainfall indices of the city where the industry is installed were analyzed. Then, the analysis of the building was performed out, studying the architectural project, the demand for drinking water and rainwater in the building, determining roof areas and the Rippl Method was used to size the reservoir. The project was developed in Qibuilder software. This way, the volumes of the lower and upper water reservoirs, diameters of vertical and horizontal rainwater conductors and gutters, diameters of columns, power of the motorpump groups and the percentage of potable water savings that is possible with the use of the system.